Sustaining human health: A requirements engineering perspective - Levy, Meira; Groen, Eduard C.; Taveter, Kuldar; Amyot, Daniel; Yu, Eric; Liu, Lin; Richardson, Ita; Spichkova, Maria; Jussli, Alexandra; Mosser, Sébastien (Journal of Software and Systems (JSS), 2023)
In our current day and age, the world suffers under the human ecological footprint, which influences our health and well-being. Technological solutions may help tackle these concerns for humanity. However, the development of such solutions requires special attention and effort in order to overcome human, political and social barriers that might prevent them from being effective. The Requirements Engineering for Well-Being, Aging and Health (REWBAH) workshop gathering in 2021 focused on addressing the challenge of how Requirements Engineering (RE) knowledge and practices can be applied to the development of information systems that support and promote long-lasting, sustained and healthier behavior and choices by individuals. An interactive discussion among subject matter experts and practitioners participating in the REWBAH’21 workshop revolved around several questions prepared by the workshop co-organizers, plus several topics brought in by the experts. In a subsequent qualitative analysis, the emerging themes were arranged in a comprehensive sustainable-health RE framework. We present our framework, which includes four main sustainable-health RE goals defined according to the changes in RE that we deem necessary for achieving a positive contribution of RE on sustainability and health. These goals are: RE Techniques, Multidisciplinary Expertise, Education Agenda, and Political Ecology. The sustainable-health RE framework supports the development of technological solutions that advance health and sustainability through these four goals, and provides a roadmap of development areas for the domain of RE. It emphasizes the complexity of developing sustainable-health solutions, the need for considering soft requirements such as emotional and social ones, as well as political considerations that may hinder implementation and stakeholder engagement. The framework also includes an educational agenda that can help requirements engineers acquire the range of capabilities that is necessary to effectively resolve the technological challenges concerning sustainability and health that lie ahead.
Keywords: Requirements Engineering; Health; Well-being; Sustainability